Kenaikan Harga Minyak Dunia dan Implikasinya Terhadap Perekonomian Indonesia di Masa Pandemi Covid-19 - Latif, Farradina; Tambunan, Nurma; Dwika Heryani, Rossi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
At the beginning of 2020, the world was shaken by a health crisis due to the spread of the covid-19 virus. This not only has an impact on health, but also on the development of the world economy, one of which is Indonesia. Economic developments in the petroleum industry play a crucial role in the Indonesian economy, as a source of income in exports and imports for the state budget as well as a source of energy (especially petroleum) to drive various sectors of life throughout Indonesia. Restricted human movement directly causes a decrease in demand for petroleum. In addition to reducing consumption, Covid-19 has also had an impact on decreasing oil and gas prices and production, including the cessation of upstream activities and a reduction in refinery activities. The recommendations put forward are oil production under the influence of Covid-19 and the profits obtained from selling it. The impact of the increase in world oil prices on the State Budget is the increasing burden of fuel subsidies and electricity subsidies. This will trigger an increase in the budget deficit or in a broader perspective will spur fiscal sustainability.